(untitled) (Nigerian Journal of Technology, 2014)
In a recent report in Science entitled “WHO IS AFRAID OF PEER REVIEW” several mentions were made of predator journals that ask for articles and publish them once a fee is paid. It is only in the complete absence of peer review that a journal can authoritatively claim to publish an article in less than six weeks from submission. Several of such journals instead of making the prestigious Thomson Reuters’ Journal Citation Reports (JCR) list now make the “Beall’s list of Predator Journals”. On weekly basis, I receive at least 10 offers for a 2-day review and editorial decision leading to eventual publication in a week if I can send in an article! What a fraud? Very high impact factor journals do not solicit for articles, they have too many to handle. The key delay between submission and publication lies where the main work is done – peer review. Peer reviewers are selected from a large pool of experts in different areas. And we, just like every journal, are continually expanding our editorial board. Some accept to review an article and either forgets to do so or is too preoccupied with other things that review reports are generally delayed. But what matters most is the review report; at least that gives the editor (and sincere authors) the assurance that the articles were subjected to academic scrutiny. This assurance is the litmus test to the article’s archival value. In order to ameliorate the delays, an article could be assigned to about seven reviewers. When three or more critical reviews (with similar reports) are received and the deadline is reached, a decision can be enacted. A well meaning author will welcome review reports with open arms even if editorial decisions are not in the affirmative. The interdisciplinary nature of NIJOTECH singles it out as a unique publication arising from Sub-Saharan Africa that is proud to be reporting original research findings from technologies that are just evolving and more relevant to the tropics. Having started since 1975, NIJOTECH has had many editors. I am privileged to be doing this job at a time when internet facilities are accessible at affordable rates. Communication between the author and editor and between the editor and reviewers has become much faster. And we now have all our past issues online, a feat we accomplished in 2012. That was just two years ago. Citations are increasing, they could not have been there if the journal were not online and it will take a little while before big indexing bodies like Scopus(R), Thomson Reuters(R), etc will key into our citations. We now publish quarterly (January, April, July and October) ensuring that on the first week of these months, the articles go on-line then we go to press. Our partners African Journal Online (AJOL) now activates our Digital Object Identifiers (DOI), one of the key ingredients for indexing. No other job can be as time consuming and at the same time exciting than to communicate and interact with people all over the world, experts in their different fields of endeavour that I may never meet. While I thank you for reading, I will welcome responses that I will publish in the next subsequent issues in this column. Engr. Prof. E. S. Obe, Editor, NIJOTECH